Activity-Based Costing Implementation for Capturing the Complexity of Manufacturing Process: The Case of CV XYZ - Firmandani, Wahyu; Arizendy Dewi Fortuna; Mochammad Nurul (TIJAB (The International Journal of Applied Business), 2024)
Background: In manufacturing companies, determining the cost of goods manufactured is more complex than in service and trading companies, considering that the production cost structure consists of direct raw material costs, direct labor costs, and factory overhead. In identifying the imposition of three components of production costs, the most difficult component to trace is factory overhead because, in determining factory overhead, various approaches and assumptions must be chosen as cost drivers, so it needs the right approach and assumptions for CV XYZ to achieve company performance. Objective: This study seeks to analyze the intricacies of factory overhead calculations under activity-based costing in comparison to the traditional plantwide rate approach used by CV XYZ, which utilizes production units as cost drivers. Method: The method used in this research is a case study on CV XYZ with interviews and documentation as data collection techniques. Interviews were conducted with accounting staff and heads of accounting departments through unstructured interviews. Documentation is carried out based on 2020 financial information. Results: The results of the analysis explain that the calculation of factory overhead applied, production costs, cost of goods manufactured (COGM), and cost of goods sold (COGS) calculated using the plantwide rate approach (production units as cost drivers) shows undercosts when compared to the activity-based costing system, so that the recognized profit is greater than it should be. The implications of undercosts cause information on the income statement to be unreliable, considering that the company has a variety of products and activities related to the production process Conclusion: The activity-based costing system uses more than one cost driver; thus, the activity-based costing system is a more accurate method to be applied by CV XYZ, which has product diversification. Keywords: Factory overhead applied, plantwide rate, activity-based costing system, profit and loss.